(untitled) (Palimpsesto, 2026)
The article critically analyzes teleworking in Chile as a work-life balance policy within the framework of Laws 21,220 and 21,645. From a feminist and territorial perspective, it argues that this modality does not guarantee a balance between work, family, and personal life, but rather deepens the care crisis, reinforces women’s double shift, and widens the territorial inequalities associated with the digital divide. It also shows how gendered organizational cultures turn work-life balance into an urban privilege. It concludes that only when linked to a national care system can teleworking contribute to social and gender justice.